THE DYNAMICS OF LAND USE AND GROUNDWATER SUSTAINABILITY: A STUDY OF ANAMBRA STATE (2017-2023) - Eze , Kingsley O; Chukwuma, Ifeoma N (International Journal of Civil Engineering and Architecture and Real Estate, 2024)
Land Use and Land Cover (LULC) changes significantly impact groundwater resources, particularly in regions experiencing rapid urbanization and agricultural expansion. In Anambra State, Southeastern Nigeria, these dynamics are crucial for understanding groundwater availability and sustainability. This study aims to analyze the temporal changes in LULC between 2017 and 2023 in Anambra State and assess their implications on groundwater recharge and dynamics. The study utilizes remote sensing data and Geographic Information Systems (GIS) to map and analyze LULC changes over seven years. The LULC categories include Trees, Rangeland, Built Area, Crops, Water bodies, Flooded Vegetation, and Bare Ground. The data are statistically analyzed to determine trends and variations in land cover types. The results indicate a significant reduction in tree cover from 1,807.49 km² in 2017 to 1,345.35 km² in 2023, accompanied by an increase in built-up areas from 1,105.26 km² to 1,329.77 km². Cropland expanded considerably from 235.03 km² in 2020 to 437.04 km² in 2023. Rangeland coverage fluctuated, peaking at 1,700.13 km² in 2022 before decreasing to 1,345.51 km² in 2023. Water bodies remained relatively stable, while Flooded Vegetation saw a significant decline from 160.13 km² in 2019 to 22.07 km² in 2023. The reduction in tree cover and the expansion of built-up areas are likely to decrease groundwater recharge due to reduced infiltration and increased surface runoff. The expansion of croplands suggests increased groundwater extraction for irrigation, potentially leading to over-extraction and depletion of groundwater reserves. The variability in rangeland and flooded vegetation areas reflects changes in land management practices, which also influence groundwater dynamics. The study highlights the critical need for sustainable land management practices to protect groundwater resources in Anambra State. The observed LULC changes pose a significant threat to groundwater recharge, emphasizing the need for policies that balance development with groundwater conservation. This study provides a comprehensive temporal analysis of LULC changes over seven years and their direct implications on groundwater dynamics in a rapidly urbanizing region.